NEW STUDENT ADMINISTRATION SYSTEM REGISTRATION DARUSSALAM AT JUNIOR HIGH SCHOOL USING VISUAL BASIC 6.0 - Nurliyana Nurliyana; Aqwam Rosadi Kardian, SKom, MM; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2004)
Darussalam  Junior High School  during this process the data by using the manual method. In this way requires very large data. The author tries to make the New Student registration Administration System using Microsoft Visual Basic 6.0.  Visual Basic 6.0. is the fastest and easiest programming language to create an application in Microsoft Windows. Visual Basic programming easier to interact directly with the element for any form of programming. As a windows based program that Visual Basic has the ability to interact with all Windows applications like Microsoft Word, Excel, Access, and so forth.